Editorial - Sparano, Eleonora; Strizzolo, Nicola; Lippolis, Martina (Community Notebook. People, Education and Welfare in the Society 5.0, 2024)
Public Relations, the subject within which reputation is taught, straddles the line between Sociology of Cultural and Communication Processes, Business Economics and Management and Social Psychology. Within this sphere, the concept of reputation has been deepened in terms of the concrete elements on which to intervene and the indicators through which to detect it. Reputation would thus be constituted by the behaviours of an organisation that, sedimented in a history, can contribute most to the perception that the various publics have of the organisation, also through targeted public relations and communication actions. From a more econo- mical point of view, reputation would represent that extra value over and above the sum of every single material and financial component of an organisation, and would support it in the face of external and internal crises, attracting talent and enabling it to achieve the highest possible price for its products or services (premium price).